Cash Holding and Company Performance in the Media & Entertainment Industry in Indonesia: Trends and Impacts Before and After COVID-19 - Fitria, Maulidah; Cahyani, Arie (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the financial performance and cash holding of media and entertainment (M&E) companies in Indonesia over the past ten years (2014-2023), with a focus on the trends and impacts of the COVID-19 pandemic. The main variables analyzed include cash holding, revenue, operating profit, and total assets. We use descriptive analysis to identify trends, and Wilcoxon Test by R Studio to test hypothesis. The results show that the M&E industry in Indonesia has experienced significant dynamics in terms of liquidity, assets, revenue, and operating income over the past decade, especially in the face of the challenges of the COVID-19 pandemic. In addition, we found significant changes in firms' cash holding during the pandemic, with an increase in average cash holding after COVID-19. This is a risk mitigation strategy and a precautionary step for M&E companies in the face of post-pandemic uncertainty. It provides important insights for financial managers and policymakers in understanding the patterns of financial performance and liquidity management in the M&E industry, especially in the face of crisis situations.